The Relationship of Spiritual and Moral Qualities with Altruistic Attitudes and Subjective Well-Being - Galina V. Ozhiganova (Peoples' Friendship University of Russia (RUDN University), 2022)
The author deals with issues related to such constructs, as 'spirituality of the personality,' 'altruism,' and 'subjective well-being.' The results of two empirical studies of the relationship of spiritual and moral qualities with (1) altruistic attitudes, and (2) with subjective well-being are presented and analyzed. In total, 262 people (students from Ufa) took part in both studies. The first study (Study 1) involved 141 people: 79 males (56%) and 62 females (44%), aged 18 to 24 years (M = 19.86; SD = 1.579). The second study (Study 2) involved 121 people: 32 males (26%) and 89 females (74%), aged 18 to 22 years (M = 19.29; SD = 0.961). The following techniques were used in the study: The Spiritual Personality Inventory by A. Husain and M. Anas (adapted in Russian by G.V. Ozhiganova); Altruistic Attitudes Questionnaire by M.I. Yasin; Satisfaction with Life Scale by E. Diener et al., and Subjective Happiness Scale by S. Lubomirsky (both of the latter techniques were adapted in Russian by E.N. Osin and D.A. Leontiev). Study 1 was aimed at identifying the relationship between indicators of the spiritual and moral qualities of a person and altruistic attitudes. The purpose of Study 2 was to find out a relationship (if any) between indicators of the spiritual and moral qualities of a person and subjective well-being. The research objectives were: (1) to establish the correlation of indicators of the spiritual and moral qualities of a person with altruistic attitudes and subjective well-being; and (2) to reveal the relationship of dif- ferent indicators of the spiritual and moral qualities with indicators of subjective well-being. The results of Study 1 showed a significant positive relationship between the spiritual and moral qualities and altruistic attitudes. Study 2 revealed a significant positive relationship between indicators of the spiritual and moral qualities and subjective well-being as well as with altruistic attitudes.